The Effects of Using Simulation-Based Learning on Problem-Solving Ability and Attitudes in Palliative Care of Nursing Student - Kesda, Rachun; Phoomilun, Phavida (Journal of Health Sciences and Wellness, 2025)
This quasi-experimental study with a single group pre- and post-test design investigated the effectiveness of learn using Simulation-Based Learning By comparing the ability to solve nursing problems. and attitudes in caring for palliative patients before and after learning using Simulation-Based Learning. The participants were 45 fourth-year nursing students enrolled in the Palliative Care Nursing Practicum course at North Bangkok University during the 2024 academic year. The research instrument comprised the Simulation-Based Learning plan developed by the researchers, a problem-solving skills assessment tool, and a palliative care attitude questionnaire. The content validity of the questionnaire was found to be .96, .85 and .89, respectively. The interrater reliability test using Cohen's Kappa showed values of .81, .86, and .95, respectively, indicating a high level of agreement among the raters. Data were analyzed using descriptive statistics and the paired samples t-test. Results showed that after the Simulation-Based Learning intervention, students demonstrated significantly higher mean scores in both problem-solving skills and positive attitudes toward palliative care (t = -17.59, -12.10, p < 0.01). These findings support the integration of Simulation-Based Learning into nursing education to enhance students’ decision-making and critical thinking skills. Simulation is a powerful tool for developing clinical skills, particularly in decision-making and problem-solving in palliative care nursing. It also fosters a positive attitude and enhances students' confidence in communicating with patients and their families, which is crucial for delivering effective palliative care that addresses the psychological and emotional needs of patients in the terminal stage of life.